PENCARIAN RUTE TERPENDEK DALAM DUNIA 3 DIMENSI BERDASARKAN ALGORITMA DIJKSTRA - Ahmad Hoirul Basori; Andi Tenriawaru (Department of Informatics, Institut Teknologi Sepuluh Nopember, 2008)
Virtual reality is one of the favorite application that very liked by peoples. Vitual reality also used in many games application in order to show the imitation of real world. Recently, virtual reality still imperfect due to shortest path problem. It need more accuration enhancement to get a very good refelection of the real world. This paper intends to discuss how to enhance the accuration of virtual reality shortest path tracking by utilizing Dijkstra algorithm. The built up prototype has three abilities: visualization, simulation fo campus traffic, and exploration of campus world in 3D ways. Keywords: 3D, virtual reality, dijkstra